2001
DOI: 10.1007/s004640000335
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic adrenalectomy in children

Abstract: The indications for laparoscopic adrenalectomy in children are benign tumors and pheochromocytomas. In these cases, laparoscopic adrenalectomy is feasible and safe, even in cases of pheochromocytoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(22 citation statements)
references
References 27 publications
1
21
0
Order By: Relevance
“…A similar conversion rate in tumor resections has been described previously [11]. Tumor extension was the reason for conversion in previous reports of thoracoscopic tumor resection as it was also in our study [12].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…A similar conversion rate in tumor resections has been described previously [11]. Tumor extension was the reason for conversion in previous reports of thoracoscopic tumor resection as it was also in our study [12].…”
Section: Discussionsupporting
confidence: 83%
“…These findings underline the need for an exact preoperative evaluation [4] and combined planning, to include both, pediatric oncologists and radiologists in the treatment strategy. Mirallié et al [11] described an easier approach for right-sided tumors in laparoscopic adrenalectomy in children. Patrick et al [12] reported a better resectability when thoracic tumors were small.…”
Section: Discussionmentioning
confidence: 99%
“…The standard objective of surgery for NB is gross total resection of primary tumor, and as long as this can be reasonably and safely achieved, MIS treatment of NB can be considered. The application of laparoscopic adrenalectomy (LA) to children has provided a number of clinical reports in which NB is prominent in the spectrum of excised adrenal pathology [10][11][12][13][14]. The largest series of LA for NB to date [15] details the safe resection of eight adrenal tumors (one attempted LA was converted to open due to tumor adherence to renal vessels) in a group of children with a mean age of 38 months.…”
Section: Discussionmentioning
confidence: 99%
“…Although longer follow-up is necessary, all patients remained clinically free of disease at a mean follow-up of 31 months [34••]. Several other reviews including fewer patients similarly discuss the feasibilities and success of the laparoscopic approach in children [29,30,35]. In addition to the short postoperative hospital stay, children and adults experience less pain and an earlier return to activity [35].…”
Section: Laparoscopic Adrenalectomymentioning
confidence: 98%
“…Successful laparoscopic adrenalectomy was first described in adults in the early 1990s [25,26]. This technique has since been adapted for use in the pediatric population, and today it is used widely in the treatment of functional, nonfunctional, benign, and malignant tumors in children [27][28][29][30].…”
Section: Surgical Therapiesmentioning
confidence: 99%